Percutaneous coronary intervention in the elderly with ST-segment elevation myocardial infarction - Gao L (Dove Medical Press, 2014)
Lei Gao,* Xin Hu,* Yu-Qi Liu, Qiao Xue, Quan-Zhou FengInstitute of Geriatric Cardiology, Chinese PLA General Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workAbstract: As a result of increased life expectancy, octogenarians constitute an increasing proportion of patients admitted to hospital for ST-segment elevation myocardial infarction (STEMI). Primary percutaneous coronary intervention is currently the treatment of choice for octogenarians presenting with STEMI. The recent literature on this topic has yielded controversial results, even though advances in drug-eluting stents and new types of antithrombotic agents are improving the management of STEMI and postoperative care. In this paper, we review the current status of percutaneous coronary intervention in the elderly with STEMI, including the reasons for their high mortality and morbidity, predictors of mortality, and strategies to improve outcomes.Keywords: octogenarians, percutaneous coronary intervention, ST-segment elevation myocardial infarction